2023
DOI: 10.3390/app13137913
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bee Bread on Antioxidant Properties, Sensory and Quality Characteristics of Multifloral Honey

Abstract: The aim of this study was to investigate the influence of bee bread addition on the phenolic content, antioxidant properties, sensory and quality characteristics of the multifloral honey. On the base of results obtained, it was stated that an enrichment of honey with bee bread led to an significant increase in total phenolic content (from 30.75 to 158.96 mg GAE/100 g), total flavonoids content (from 2.77 to 21.15 mg QE/100 g), and phenolic acids content (from 11.02 to 35.47 mg CAE/100 g). Gallic acid was the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…This finding differs from Habryka et al who found that increasing bee bread content improves TAC value in honey. They also indicated that as the addition of bee bread increases, the acceptability of the taste decreases, which is similar to the findings of the present study . Marsoul et al indicated that the TPC of P.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding differs from Habryka et al who found that increasing bee bread content improves TAC value in honey. They also indicated that as the addition of bee bread increases, the acceptability of the taste decreases, which is similar to the findings of the present study . Marsoul et al indicated that the TPC of P.…”
Section: Resultssupporting
confidence: 91%
“…Habryka et al indicated that taste acceptability decreased with increasing addition of bee bread. This is similar to the results of the present study Table shows the highest general acceptability value (7.90 ± 0.34) with the treatment of bee bread content 20 mg/100 mL, ultrasound time (8 min), and ultrasound power (60 amplitude) (Run No.…”
Section: Resultsmentioning
confidence: 99%
“…The palynological profiles of the BB from this study varied, and it was challenging to differentiate the samples according to phenolic profiles and predominant families and correlate them with the preceding BB studies/research. However, the literature data confirm the PCs depicted in Table 2 [15,25,43,71,97,98]. The presence of PCs was also confirmed by FTIR analysis (Figure 4).…”
Section: Phenolic Compound Profiles By Uhplc-dad-esi/mssupporting
confidence: 71%
“…The sensory quality and health-promoting properties of honey can be shaped by various types of additives, most often introduced to it during the creaming process [1][2][3][4]. The process of creaming honey consists of obtaining it in a crystallized form under controlled conditions, thanks to which a smooth consistency is obtained, suitable for mixing with various additives.…”
Section: Introductionmentioning
confidence: 99%
“…Bee bread, a form of pollen processed by bees, has nutritional, antioxidant, hypolipidemic, hepatoprotective, anticancer, antimicrobial, and antiviral properties due to its high content of protein, sugars, and lipids [6][7][8]. Due to its unattractive sensory properties, mixing it with honey has been well-known for a long time and it was traditionally used by beekeepers practices which allow the introduction of bee bread to the diet [4]. The addition of bee bread to honey is usually high, most often 10-20% (w/w), but the literature gives examples of 60% share [1].…”
Section: Introductionmentioning
confidence: 99%